Evaluation of organic control methods of the bean beetle Ootheca bennigseni in East Africa - Paul, U.V.; Ampofo, J.K.O.; Hilbeck, A.; Edwards, P. (New Zealand Plant Protection, 2007)
Dry beans (Phaseolus vulgaris) are a major source of dietary protein and calories for the poor in East Africa The increasingly abundant Ootheca bennigseni (Coleoptera Chrysomelidae) is a key pest that threatens bean production and jeopardizes farmers harvest Participatory research with farmers suggested the need for affordable and accessible organic pest control methods The effect of diluted cow urine and aqueous extract from vernonia (Vernonia lasiopus var iodocalyx) leaves was evaluated in three consecutive applications Researchermanaged onfarm trials showed that cow urine reduced pest abundance for at least 24 hours The aqueous vernonia extract reduced the insect abundance consistently for at least 7 days Foliar damage at the peak time of infestation was significantly reduced by vernonia but not by cow urine Future research needs to find ways to enhance and prolong the efficacy of natural substances and determine the relationship between adult abundance larval population and bean yield